Economic Function and Financial Literacy of Modern Family - Pejkovski, Jovan; Pejkovska, Mirjana Kaeva (European Journal of Economics and Business Studies, 2019)
The economic function of the family is expressed in the provision of material subsistence for its members, in the provision and consumption of subsistence. The paper looks at the post-modern urban family's placement in terms of means of production and its consumption role.How are the functions of the modern family related to providing and meeting the needs of members? Is there a model for economic insurance of family income that builds its stability and sustainability? How to realize the family's desire to raise their standard of living? What are the forms of economic cooperation within the family? These and other issues related to fulfilling the economic role of the family is the subject of an analysis in the paper on the basis of several elements and issues that are constantly relevant.The paper particularly recognizes the importance of financial literacy for family members. How to develop and on what grounds to base people's financial cognition? What is the knowledge to create and manage a family budget as a detailed overview of finances? The formation of economic and financial education is perceived as the basis for improving personal and family finances. At what level and by what methods can the financial knowledge of family members be improved? Financial literacy limits the opportunities for growth, development, and satisfaction of the needs of the family and its members.The paper analyzes the role of the educational institutions in raising the economic and financial literacy of the members of the modern family that is of interest to any society. The economic function of the family is also considered in the context of constant social changes and external influences that limit the possibilities of family members. Only educated and skilled individuals can manage social processes and influence standard-raising.
Keywords: family, economic function, financial literacy, family finances and personal finances